2017
DOI: 10.15406/ipcb.2017.02.00030
|View full text |Cite
|
Sign up to set email alerts
|

Syndemic Approach in Preventing Perinatal Near Miss before First Phase of Three Delay Model

Abstract: Perinatal near miss covers the maternal and neonatal morbidity that refers to two targeted group of mother and baby. Maternal and perinatal mortality are two health indicators that showed very wide gaps of achievement by types of country based on income according to MDG achievement in 2015. The risk of a woman in a developing country dying from a maternal-related cause during her lifetime is much higher compared to a woman living in a developed country. Even though pattern of mortality shows declining trend in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(32 reference statements)
0
0
1
Order By: Relevance
“…22 However, the drastic increment of 20% in the previous year differs from the crude birth rate increment of about 1.1%. 23 The trend in this study was better than the hospital-based prevalence rate reported in a cohort study in a tertiary teaching hospital in Nigeria which was 120 in 1000 population in 2009 19 as opposed to the incidence in this study centre which never exceeded 115 in 1000 population across the five years. The difference, however, may be due to the policy of the Nigerian teaching hospital which only accepted complicated pregnancy referrals as opposed to our centre which also accepts normal deliveries for undergraduate teaching purposes.…”
Section: Discussioncontrasting
confidence: 69%
“…22 However, the drastic increment of 20% in the previous year differs from the crude birth rate increment of about 1.1%. 23 The trend in this study was better than the hospital-based prevalence rate reported in a cohort study in a tertiary teaching hospital in Nigeria which was 120 in 1000 population in 2009 19 as opposed to the incidence in this study centre which never exceeded 115 in 1000 population across the five years. The difference, however, may be due to the policy of the Nigerian teaching hospital which only accepted complicated pregnancy referrals as opposed to our centre which also accepts normal deliveries for undergraduate teaching purposes.…”
Section: Discussioncontrasting
confidence: 69%